Motivno-tematski preplet v delu Petra Svetine - Babšek, Andreja (Revija za elementarno izobraževanje, 2009)
Themes and motifs in the works of Peter Svetina. The work of Peter Svetina shows diversification and complexity from both scientific and artistic aspects. The article focuses on the author's forma) variety of writing, which is accented by some motifs that are threaded through his complete works: the library, the eros-tanatos relationship, Christian mysticism and artistic creation. The central works in this line are The first floor cafe (Kavarna v prvem nadstropju) and Cicadas silence at midnight (Škržati umolknejo opolnoči), even though there is no doubt to the vitality and artistic value of his other writings. Svetina's works mainly focus on depicting a world that lacks beauty, however he imbues it with gentleness and spices it with humour.